2001
DOI: 10.2139/ssrn.269789
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Private Equity Fundraising in Western Europe

Abstract: A B S T R A C TThe aim of this paper is to identify the key factors that lie behind venture capital/private equity fundraising in countries where there is scarce and asymmetric information about final returns. The main contribution of this paper is to explain fundraising by means of variables directly related to the venture capital process rather than by macroeconomic ones. We use panel data techniques on data from 16 European countries during the nineties. In the light of the long period required for investin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…Jeng and Wells (2000) analyse the determinants of venture capital for a sample of 21 countries and find that innovation is not a significant item, while the IPO opportunity represents the strongest driver of venture capital investment. Balboa and Marti (2001) try to identify the key factors that lie behind venture capital/private equity fundraising in countries where there is scarce and asymmetric information about final returns. The main contribution of their analysis is that it explains fundraising by means of variables directly related to the venture capital process rather than by variables related to the economic environment, but, in conclusion they reach the same conclusions as Jeng and Wells (2000) about the relationship between innovation and private equity investment decisions.…”
Section: Institutional Framework On Venture Capital Innovation Anmentioning
confidence: 99%
“…Jeng and Wells (2000) analyse the determinants of venture capital for a sample of 21 countries and find that innovation is not a significant item, while the IPO opportunity represents the strongest driver of venture capital investment. Balboa and Marti (2001) try to identify the key factors that lie behind venture capital/private equity fundraising in countries where there is scarce and asymmetric information about final returns. The main contribution of their analysis is that it explains fundraising by means of variables directly related to the venture capital process rather than by variables related to the economic environment, but, in conclusion they reach the same conclusions as Jeng and Wells (2000) about the relationship between innovation and private equity investment decisions.…”
Section: Institutional Framework On Venture Capital Innovation Anmentioning
confidence: 99%
“…Several studies have used panel data analysis to study the effects of several subsets of our variables discussed in the previous section (Félix et al ., 2013; Balboa and Martí, 2001; Bengoa and Sanchez-Robles, 2003; Bonini and Alkan, 2011; Cherif and Gazdar, 2011; Herrera-Echeverri et al ., 2014; Bedu and Montalban, 2014; Groh and Wallmeroth, 2016; Herrera-Echeverri, 2017). We use panel data analysis because of the time series and cross-sectional nature of the data collected over two decades.…”
Section: Methodsmentioning
confidence: 99%
“…The most pertinent studies on this topic were conducted by Gompers and Lerner (1998), Jeng and Wells (2000), Balboa and Martí (2001), Balboa and Martí (2003), Schertler (2003) Gompers and Lerner (1998) have shown that better GDP growth, higher R&D spending, and a lower capital gains tax led to more venture capital. Jeng and Wells (2000), on the other hand, found that neither GDP growth nor market capitalization were important venture capital drivers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As demonstrated by Balboa and Martí (2001), Schertler (2003), Kelly (2012), Bernoth and Colavecchio (2014), and Henchiri (2016), most of the research examining the determinants and drivers of PE activity uses funds raised and invested as the target variables. And thus, to study the drivers of private equity, we employ these two target variables as well: Fundraising & Investments.…”
Section: Target Variablesmentioning
confidence: 99%